Rice Production Structures in Sri Lanka: The Normalized Translog Profit Function Approach - Wijetunga, Chatura Sewwandi (Asian Journal of Agriculture and Rural Development, 2016)
This study attempts to estimate the output supply and input demand elasticities of rice production using the restricted normalized translog profit function for the four major paddy producing districts; Anuradhapura, Hambantota, Kurunegala and Polonnaruwa in Sri Lanka. In addition, elasticities of substitution between inputs are also estimated. The results suggest that the changes in market prices of inputs and output significantly affect the farmers’ profits, rice supply and the use of resources in paddy cultivation. The supply elasticity of rice with respect to its own price is 0.5 and the supply elasticity of output with respect to fertilizer price is -0.05 on an average. Fertilizer demand in the country is inelastic but significant to its own price. Therefore, fertilizer subsidy is one of the main factors to increase fertilizer demand as well as paddy supply in the country. In addition, the low elasticity of substitution between labour and fertilizer and other inputs indicates that there is a complementary relationship among these inputs hence their combined application increases paddy production synergistically. Overall, this study suggest that farmers are price sensitive and assures prevalence of higher output price is essential for higher rice production.